Inbreeding depression on production and reproduction traits of buffaloes from Brazil - Malhado, Carlos Henrique Mendes; Malhado, Ana Claudia Mendes; Carneiro, Paulo Luiz Souza; Ramos, Alcides Amorim [UNESP]; Carrillo, José Adrián; Pala, Akin (Wiley, 2013)
The objective of this study was to evaluate the influence of inbreeding depression on traits of buffaloes from Brazil. Specifically, the traits studied were body weight at 205 and 365 days of age, average daily gain from birth to 205 days (ADG_205), average daily gain between 205 and 365 days (ADG205_365) in Mediterranean buffaloes, and milk yield, lactation length, age of first calving and calving intervals in Murrah buffaloes. Inbreeding effects on the traits were determined by fitting four regression models (linear, quadratic, exponential and Michaelis-Menten) about the errors generated by the animal model. The linear model was only significant (P<0.05) for growth traits (exception of ADG205_365). The exponential and Michaelis-Menten models were significant (P<0.01) for all the studied traits while the quadratic model was not significant (P>0.05) for any of the traits. Weight at 205 and 365 days of age decreased 0.25kg and 0.39kg per 1% of increase in inbreeding, respectively. The inbred animals (F=0.25) produced less milk than non-inbred individuals: 50.4kg of milk. Moreover, calving interval increased 0.164 days per 1% of increase in inbreeding. Interestingly, inbreeding had a positive effect on age at first calving and lactation length, decreasing age of first calving and increasing lactation length. © 2012 Japanese Society of Animal Science.
Keywords: Buffalo; Growth; Inbreed accumulation; Milk yield; Animalia; Bubalus